The Effect of Passing Training Using Ankle Weights with the Rondo Training Method on Improving Futsal Players Passing Accuracy - Daffa' Rizqullah; Dikdik Zafar Sidik; Mulyana (Jurnal Pendidikan Jasmani (JPJ), 2026)
Improving passing accuracy is an important aspect in futsal, because passing is a vital basic technique for futsal to run smoothly. The underlying problem of this study is the low level of passing accuracy in futsal players at SMAN 1 Margaasih, which often results in loss of ball possession during matches. This study aims to determine the significant effect of passing training using ankle weights with the rondo training method on improving passing accuracy in futsal players. This study uses a quantitative approach with an experimental method using a one-group pretest-posttest design. The research sample consisted of 18 futsal players at SMAN 1 Margaasih who were selected by purposive sampling. The instrument used to measure passing ability was the Wall Pass Test which had been modified according to the research needs. The results showed a significant increase in passing accuracy after being given treatment. This was proven by the paired sample t-test statistical test which showed a significance value (p-value) smaller than α = 0.05, which means that H₁ is accepted and H₀ is rejected. Rondo training provides a stimulus in the form of pressure and quick decision-making in tight spaces, while ankle weights provide the effect of increasing leg muscle strength and explosive power, which synergistically improves the player's technical and physical ability to pass accurately.